The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1111/ejn.14934
|View full text |Cite
|
Sign up to set email alerts
|

Poly I:C‐induced maternal immune challenge reduces perineuronal net area and raises spontaneous network activity of hippocampal neurons in vitro

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 96 publications
(128 reference statements)
0
12
0
Order By: Relevance
“…Similarly, a reduced firing frequency and increased amplitudes of miniature excitatory postsynaptic currents (mEPSPs) in the hippocampal CA1-region of mice derived from Poly I:C- treated dams could be observed in hippocampal slices [ 206 ]. In addition, dissociated hippocampal neurons isolated from embryonic mice of Poly I:C-treated dams developed a network hyperactivity and disruptions of perineuronal nets (PNNs), as well as reduced soma areas of PNN-wearing neurons in vitro [ 207 ]. PNNs are a specialized and condensed form of the extracellular matrix (ECM) that stabilize synaptic contacts but prevent the formation of new connections [ 208 ].…”
Section: Structural and Functional Hippocampus Deviations In Animal M...mentioning
confidence: 99%
“…Similarly, a reduced firing frequency and increased amplitudes of miniature excitatory postsynaptic currents (mEPSPs) in the hippocampal CA1-region of mice derived from Poly I:C- treated dams could be observed in hippocampal slices [ 206 ]. In addition, dissociated hippocampal neurons isolated from embryonic mice of Poly I:C-treated dams developed a network hyperactivity and disruptions of perineuronal nets (PNNs), as well as reduced soma areas of PNN-wearing neurons in vitro [ 207 ]. PNNs are a specialized and condensed form of the extracellular matrix (ECM) that stabilize synaptic contacts but prevent the formation of new connections [ 208 ].…”
Section: Structural and Functional Hippocampus Deviations In Animal M...mentioning
confidence: 99%
“…The culturing of primary hippocampal neurons was performed, as previously described (Gottschling et al, 2016;Wegrzyn et al, 2020). The hippocampi of embryonic stage 15.5 (E15.5) mice were isolated and collected in 1 ml dissection medium [(HBSS, Thermo Fisher Scientific Inc.;Cat.…”
Section: Culturing Of Primary Hippocampal Neuronsmentioning
confidence: 99%
“…PNN area sizes were quantified using the "Freehand Selections" tool in ImageJ after defining a distance length depending on the scale bar. The fluorescence intensity of PNNs was analyzed by measuring the mean gray value and on the other hand by determining the total corrected total cell fluorescence (CTCF), as previously described (McCloy et al, 2014;Wegrzyn et al, 2020).…”
Section: Data Quantificationmentioning
confidence: 99%
“…Wegrzyn et al. (2020) from the Faissner group provide insights into the ECM and cellular mechanisms of the maternal immune system during gestation, which is well known to be linked to neuropsychiatric diseases like schizophrenia. By using behavioral tests, primary astrocytic and neuronal cell cultures, immunocytochemistry and electrophysiological recordings, the researchers observed that treatment with polyinosinic‐polycytidylic acid sodium salt (Poly I:C), a model of viral infection, resulted in impairment of prepulse inhibition, a significantly reduced axonal complexity and a significant reduction of the major ECM molecule aggrecan with regard to staining intensity, area and soma size.…”
mentioning
confidence: 99%